Cracking in drying latex films - Tirumkudulu, Mahesh S (Langmuir : the ACS journal of surfaces and colloids, 2005)
Thin films of latex dispersions containing particles of high glass transition temperature generally crack while drying under ambient conditions. Experiments with particles of varying radii focused on conditions for which capillary stresses normal to the film deform the particles elastically and generate tensile stresses in the plane of the film. Irrespective of the particle size, the drying film contained, simultaneously, domains consisting of a fluid dispersion, a fully dried packing of deformed spheres, and a close packed array saturated with water. Interestingly, films cast from dispersions containing 95-nm sized particles developed tensile stresses and ultimately became transparent even in the absence of water, indicating that van der Waals forces can deform the particles. Employing the stress-strain relation for a drying latex film along with the well-known Griffith's energy balance concept, we calculate the critical stress at cracking and the accompanying crack spacing, in general agreement with the observed values